Pregnanediol urinary d-norgestrel postcoital - Kesseru, Esteban (2015)
The effect of the administration of D-Norgestrel on urinary excretion postcoital pregnanediol studied and found to not act as said progestin anovulatory at least to a limited extent delivered dose cycle.